ئەدەبى منداڵ و ڕۆڵى ڕاگەیاندن لە گەشەکردنیدا - محمود, فاضل مجید (Sulaimani Journal for Humanities, 2003)
Child is an active and full of life living being, he is capable to acquire skills and knowledes quickly and he has his special world.his birth gives many meanings to the life, it renews life and helps the humanity to continue,so the child should be paid attention do,and should be brought up according to the moderen methods and theories in away that fit with his age;morover he should be brought upin asound and suitable inveronment. It is true that the family is thre first plase where the child is raised but it is not enough to raise him perfctily, because the child's world is not restricted to his family only but there are many other important sourcea that have the same duty e.g.the mass media, media institutions can play amain role in this respect. In order to do their duty perfectly, we intended to give the mass media some recommendations and notes in this filed, through which we talked about the media sources and channels and their direct and indirect impact on the child. In fact their programs should be in away that the child, his family, society and allthe humanity can make use of them. We dealt with the most important sources like press, television and broadcast, and their duty to present special and important subjectsconcerning the child to achieve his aim, wich is raising the child soundly and over coming the obsticals in this respect. Finally we registered our notes about each channel's work and we determined the research's results through a number of points so that we can serve the society genrally and children soecially because they are future's generation.